Aesseal supplies and repairs mechanical seals for Total refinery. Issue 9 (September 2016) - Unknown
Abstract : In the UK, Aesseal Plc has been awarded a five-year managed reliability contract that covers the use of mechanical seals at the Lindsey Oil Refinery, in Killingholme, Lincolnshire, owned by Total Sa.